2018
DOI: 10.1021/acs.jpcc.7b11190
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Investigations of the Effects of Si/Al Ratio and Al Distribution on the Adsorption Selectivity of n-Alkanes in Brønsted-Acid Zeolites

Abstract: The adsorption of n-alkanes onto Brønsted-acid sites is a key step in the catalytic cracking of alkanes. Employing configurational-bias Monte Carlo simulations, we have investigated how the ratio of equilibrium adsorption constants for central C−C bonds relative to terminal bonds of n-alkanes (i.e., the adsorption selectivity ratio) in Brønsted-acid zeolites is influenced by the Si/Al ratio and the Al distribution. A new computational approach was implemented, and the developed force field was validated by a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 59 publications
1
41
0
Order By: Relevance
“…[2] to account for the interaction of the proton with the reactant-state alkane (i.e.,a lkane molecules adsorbed at Brønsted protons) in CBMC simulations by modifying the Lennard-Jones force field parameters for the oxygen atoms attached to the Al atom. The accuracyo ft his potential is furtherc onfirmed in our recent work [7] by comparing CBMC-calculated values of the adsorption enthalpya nd entropyf or reactant-statea lkanesw ith experimentally measured values for severalz eolite structures (MFI, TON, FER, MWW,M OR,K FI, and FAU). We note that as pecific and explicit model toc apture the directionality of hydrogen bondsm ay be difficult given the tendency of the proton to move rapidly amongst the four oxygen atoms at reaction temperatures.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…[2] to account for the interaction of the proton with the reactant-state alkane (i.e.,a lkane molecules adsorbed at Brønsted protons) in CBMC simulations by modifying the Lennard-Jones force field parameters for the oxygen atoms attached to the Al atom. The accuracyo ft his potential is furtherc onfirmed in our recent work [7] by comparing CBMC-calculated values of the adsorption enthalpya nd entropyf or reactant-statea lkanesw ith experimentally measured values for severalz eolite structures (MFI, TON, FER, MWW,M OR,K FI, and FAU). We note that as pecific and explicit model toc apture the directionality of hydrogen bondsm ay be difficult given the tendency of the proton to move rapidly amongst the four oxygen atoms at reaction temperatures.…”
mentioning
confidence: 78%
“…[2] Activation energy [kJ mol À1 ] [a] Activation entropy[ Jmol À1 K À1 ] [a] Kadam et al [1] Janda et al [2] Kadametal. [1] Janda et al [2] FER 187(2)1 79 (7) 12(4) À7(9) TON 187(2)1 80 (7) 10(4) À8(9) CHA 187(2)- [b] À6 (2) -[b] MFI 187(2)1 84 (7) We next clarify and correctsome minor errors in the descriptions of our previous conclusions [2] given by Kadam et al [1] The authorss tate that we have suggested based on combining molecular simulations and experimental cracking rate measurements that structure-activity relationshipsa re explained in generalb yc hanges in the intrinsic activation energies, and not the intrinsic activation entropy. In fact, our conclusions regarding this subjectd epend on the monomolecular reaction pathway ando nt he alkane in question.S imilar to Kadam et al,f or n-butane central cracking we proposed that the intrinsic rate of reaction is controlled by the intrinsic activation entropy, which becomesl ess negative as the confinement increases for zeolite structures possessing 10-MR channels andd iffering in the size and abundance of intersections or cages.…”
mentioning
confidence: 99%
“…The lower concentration of Lewis acid sites in β G/HNO3 reduced the dehydrogenation of alkanes, thereby providing a highly paraffinic fraction. The setting of Al atoms and their spatial proximity also affect the adsorption selectivity and, therefore, the selectivity of the overall catalytic process [36,37]. Adjacent Brønsted acid sites favor cracking over dehydrogenation, as well as central cracking over terminal cracking.…”
Section: Catalytic Performance: Thermogravimetric and Operando Ir Stumentioning
confidence: 99%
“…The potential interactions of different acid sites might also affect the acidic properties of individual acid sites. The short‐range effect stemming from spatial proximity of adjacent Brønsted acid sites has been investigated by 1 H double quantum (DQ) MAS NMR, 13 C MAS NMR, Co(II) ion UV‐vis DRS or computational chemistry method 33‐35 . Although less mentioned, the long‐range interaction of different acid sites has also been primarily revealed by 1 H MAS NMR 36,37 .…”
Section: Introductionmentioning
confidence: 99%
“…The shortrange effect stemming from spatial proximity of adjacent Brønsted acid sites has been investigated by 1 H double quantum (DQ) MAS NMR, 13 C MAS NMR, Co(II) ion UV-vis DRS or computational chemistry method. [33][34][35] Although less mentioned, the long-range interaction of different acid sites has also been primarily revealed by 1 H MAS NMR. 36,37 In common, the above-mentioned investigations on the spatial distribution of acid sites is predominately based on the characterization of the local chemical environment of individual acid sites.…”
Section: Introductionmentioning
confidence: 99%